Synthesis and characterization of polyimides containing 4,4'-hexafluoroisopropylidene-bisphthalic - Hung,Daniel Liu Chun (1999)
This paper presents the synthesis and characterization of polyimides, which contain a 4,4'-hexafluoroisopropylidene-bisphthalic anhydride (6FDA) unit in the backbone. These polyimides are a result of the use of the traditional method of "one step". The reactions occur between equimolar of a dianhydride and an aromatic diamine in presence of the solvent dimethylacetamide (DMAc), then cyclo-dehydrided by adding the acetic anhydride and pyridine. In this work, the 6FDA was used as the dianhydride and four different diamines were investigated: 3,3',5,5'-Tetramethyl-2,2- bis[4-( 4-aminophenoxy) phenyl] propane; 2,2-bis[4-(4-aminophenoxy)-phenyl] hexafluoropropane; 1,3-bis(4-aminophenoxy)benzene and 2,2'-dimethyl-4,4'-bis(4-aminophenoxy)biphenyl. The four polyimides (PA, PB, PC and PD) were characterized by tensile strength, infrared, inherent viscosity, Differential Scanning Calorimeter (DSC) to get the glassy transition temperature (Tg) and Gel Permeation Chromatograph (GPC) to obtain the average molecular weight (Mn).